2001
DOI: 10.1897/1551-5028(2001)020<2081:aisotu>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Interlaboratory Study on the Use of Steroid Hormones in Examining Endocrine Disruption

Abstract: In recent years, there has been an increased use of the measurement of sex steroid hormone levels in the blood of animals exposed to chemicals as an indicator of reproductive impairment or an alteration in endocrine function. Although levels of hormones are often compared among animals and laboratories, there has been no study to examine the between-laboratory variability in actual steroid measurements. Therefore, we initiated a study with white sucker collected from a site receiving pulp mill effluent, previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Males downstream had significantly ( p ϭ 0.004) higher plasma estradiol concentrations compared with those at the upstream site on the Conococheague. Whereas concentrations of reproductive hormones are useful indicators for disruption of the reproductive cycle [24], these concentrations often are confounded by natural fluctuations and environmental factors, such as water temperature influenced by rain and runoff events [25]. Concentrations of testosterone and estradiol in male SMB have been reported previously at 1 ng/ ml or less during this time of year in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Males downstream had significantly ( p ϭ 0.004) higher plasma estradiol concentrations compared with those at the upstream site on the Conococheague. Whereas concentrations of reproductive hormones are useful indicators for disruption of the reproductive cycle [24], these concentrations often are confounded by natural fluctuations and environmental factors, such as water temperature influenced by rain and runoff events [25]. Concentrations of testosterone and estradiol in male SMB have been reported previously at 1 ng/ ml or less during this time of year in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Histologic observations within the gonads such as atresia, foci of pigmented cells, and gamete stage also are useful [22]. Lastly, physiological measures of plasma vitellogenin (VTG) [23] and sex steroid hormone concentrations are common endpoints of endocrine disruption [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Depressions in circulating steroids in wild fish exposed to pulp mill effluent have been documented since the late 1980s [1][2][3]24,[30][31][32][33]. Steroid depressions are one of the most consistent responses associated with exposure to final effluents and are highly correlated with other reproductive abnormalities [34]. Although industry-wide process changes in the last decade have reduced acute toxicity and organochlorine discharges, reproductive effects in wild fish, including steroid depressions, continue to be observed at several sites in Canada [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Although shorter-term (days to weeks) ethynyl estradiol-exposure studies have shown elevated circulating vitellogenin concentrations in association with a reduction or cessation of spawning in exposed male fish relative to controls [32], results from other studies [28] show that long-term exposure to strong estrogens may activate physiological regulating mechanisms that make vitellogenin a less sensitive indicator of endocrine disruption. In addition, high variability in sex steroids and vitellogenin has been documented in other studies [33], including in unexposed control fish [21,34]. Numerous factors have been shown to contribute to variability in these endpoints including handling stress, gonadal maturation, and time of day [33,35,36], although analysis of fish tissues rather than blood plasma concentrations is thought to control for some of these [37].…”
Section: Discussionmentioning
confidence: 99%